An ecological model of invasion and metastasis - Serrano, José J.; Urdiales-Ruiz, José Luis; Medina-Torres, Miguel Ángel; Montañez, Raúl (My University, 2017)
It has been argued that malignat tumours represent complex dynamic and self-organizing ecosystems. Furthermore, there is increasing evidence that collective cell migration occurs during invasion and metastasis. Here, we propose a mathematical model showing how cooperative behaviour could arise in heterogeneous tumour populations and why the emergence of such swarm-like patterns would confer advantageous properties to the spatio-temporal expansion of tumours. consequently, targeting such collectivity should be of interest for basic knowledge and clinical tratment of cancer, including rare tumours.
Keywords: Cáncer; Metástasis; Invasion; Ecological model; Metastasis